2019
DOI: 10.5114/fn.2019.86299
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside IV protects neurons from microglia-mediated cell damage through promoting microglia polarization

Abstract: Astragaloside IV (AST-IV) is a major active ingredient of astragalus, with a neuroprotective effect. The current study is aimed to investigate the impact of AST-IV on the M1/M2 microglial activation in response to lipopolysaccharide (LPS) stimulation, how AST-IV attenuated microglia-mediated neuronal damage, and the molecular mechanisms underlying AST-IV's protection of neurons against microglia-mediated neuronal damage. Our results showed that AST-IV partially protected microglia from death evoked by LPS and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…In LPS induced BV2 and primary microglia cells, AS-IV could significantly reduce the release of inflammatory mediators through activating NRF2/HO-1 via ERK signaling pathway 34) . In a report investigating the effect of AS-IV on the microglia activation stimulated by LPS, AS-IV was found to exert anti-inflammatory effect through inhibiting TLR4/NF-κB pathway and converting microglia from inflammatory M1 phenotype to anti-inflammatory M2 phenotype 35) . Moreover, it was reported that AS-IV inhibits microglial activation partially by activating glucocorticoid receptor mediated signaling pathway 36) .…”
Section: Discussionmentioning
confidence: 99%
“…In LPS induced BV2 and primary microglia cells, AS-IV could significantly reduce the release of inflammatory mediators through activating NRF2/HO-1 via ERK signaling pathway 34) . In a report investigating the effect of AS-IV on the microglia activation stimulated by LPS, AS-IV was found to exert anti-inflammatory effect through inhibiting TLR4/NF-κB pathway and converting microglia from inflammatory M1 phenotype to anti-inflammatory M2 phenotype 35) . Moreover, it was reported that AS-IV inhibits microglial activation partially by activating glucocorticoid receptor mediated signaling pathway 36) .…”
Section: Discussionmentioning
confidence: 99%
“…It also modulates ERK and NF-κB pathways, decreases levels of proinflammatory cytokines in the brain and reduces neuroinflammation (Lin et al, 2019 ). Astragaloside IV (AST-IV) can exert anti-inflammatory effects on microglia by inhibiting the TLR4/NF-κB signaling pathway and promote the transformation of microglia to a neuroprotective M2 phenotype (Yu et al, 2019 ). In addition, QMAD, a dichloromethane soluble fraction of the Chinese herb QuMai, induces Tregs by altering intracellular signaling that restricts AKT phosphorylation (Reid-Adam et al, 2013 ), which may be a new strategy for the treatment of ALS.…”
Section: Therapeutic Strategies For Neurodegenerative Diseasesmentioning
confidence: 99%
“…Panax ginseng extract and ginsenoside Rg1 significantly suppressed the signaling transduction pathway of TLR3 and TLR4 and decreased the inflammation factors induced by A β 25-35 in neuroglial NG108-15 cell culture [ 222 ]. Astragaloside IV exerted anti-inflammatory effects on microglia by inhibiting TLR4/NF- κ B signaling pathways and protected neurons from microglia-mediated cell death through microglia polarization [ 223 ]. Ginkgo diterpene lactones alleviated LPS-induced inflammatory response in primary astrocytes by downregulation of the TLR4/NF- κ B signal pathway [ 224 ], and ginkgolide B alleviated learning and memory impairment in rats with vascular dementia by reducing neuroinflammation due to decreased activity of the TLR4/NF- κ B pathway [ 225 ].…”
Section: Reducing Inflammationmentioning
confidence: 99%